(untitled) (Muitas Vozes, 2022)
This paper presents the results of a qualitative research whose objective was to investigate how teacher educators and student-teachers of the Portuguese-English Languages major at a Brazilian public university perceived their local practices involving multiliteracies, English as a lingua franca (ELF) and translingual practices. The data analysis indicated that participants conceived multiliteracies as teaching resources, rather than a perspective on what languages are and how they work. Proficiency was generally linked to the correct use of a “norm” and to emulation of the native-speaker construct. However, when referring to intelligibility, participants declared to appreciate the importance of being able to negotiate meanings in each interactive situation, associating intelligibility with English as a lingua franca. Translingual practices were considered as consequences of a poor command of English and should be avoided and corrected, especially when happening in writing. As we anticipated, participants were not a coherent whole in their praxis related to teaching and learning English, as they seemed to value contradictory views of language, depending on the situation we presented them with. This finding shows that they were highly sensitive to context and willing to appreciate its importance in their praxis.